The Succession of mycobiota on the various off ground components of wheat crop residues - RAJ SINGH,; SUSHIL KUMAR UPADHYAY,; AMIT KUMAR,; ANJU RANI,; PERMOD KUMAR, (International Journal of Pharma and Bio Sciences, 2019)
The utmost mechanism of the life cycle of any individual species is the decomposition of their dead remains. Therefore, the post harvested leftovers or dead remains approaches to decompose and the nutrients locked up in the litter thereafter a number of new substances synthesized during the decomposition may also percolate to the soil profile. Similar to so many agricultural post harvested residues, the wheat straw also consists of lignified cell wall material, cellulose, hemicellulose, pectin and lignin. The process of transformation and decomposition of post harvested wheat crop residues involve the intervention of microorganisms. The present study revealed decomposer mycobiota on different components of wheat crop residues i.e. internodes, leaves chaff and combined straw. Sum of 48 forms of fungi have been isolated from above ground residues of wheat crop decomposing under soil throughout 390 days study (May 2015 to May 2016) to achieve its maximum result of decomposition of lignocellulosisc residues as lignin is the most recalcitrant component of the ligocellulosic biomass of upper ground parts of the wheat crop. Out of 48 isolated fungi, two sterile forms which failed to sporulate were also identified during investigation. The remaning 46 forms of fungi that have potential to sporulated could be identified and classified by the application of morphotaxonomical tools. The genera and species within a family are arranged in alphabetical order. The identified fungi belong to Zygomycetes (two forms), Plectomycetes (two forms), Pyrenomycetes (three forms) and thirty nine from Hyphomycetes. The findings were reflected the resource-specificity of fungal species. The author hypothesized and believed that the resource-specificity attributed to the balance of definite biochemical in the crop residues having the regulatory effect on diversity and succession of mycobiota. The anatomical structures of the resources (post harvested wheat crop residues) were found to have a profound influence on the succession of mycobiota. The pattern of microbial colonization of decomposing wheat crop residues facilitates to develop a strategy to utilize current lignocellulosic waste for the formulation of biodecomposer, cultivation of single cell proteins(medicinal value), mushrooms(nutritional supplement) and production of biogas and alcohol (green fuel).